Implementation of a Web-based remote control system for qZS DAB application using low-cost ARM platform - Korzeniewski, M.; Kulikowski, K.; Zakis, J.; Jasinski, M.; Malinowski, A. (Bulletin of the Polish Academy of Sciences. Technical sciences, 2016)
Continuous development of intelligent network applications drives the demand for deployment-ready hardware and software solutions. Such solutions are highly valued not only by distributed producers of energy but by energy consumers as well. The use of intelligent network applications enables the development and improvement of the quality of services. It also increases self-sufficiency and efficiency. This paper describes an example of such device that allows for the control of a dual active bridge (DAB) converter and enables its remote control in real time over an IP-based network. The details of both hardware and software components of proposed implementation are provided. The DAB converter gives a possibility to control and manage the energy between two DC power systems with very different voltage levels. Not only information, but also the quality of energy, the direction of power flow, and energy storage systems can be easily controlled through an IP-based network and power electronics converters. Information technology, together with intelligent control of power electronics technology, provides a flexible solution, especially for sustainable smart grids.